Predictors of Seasonal Flood Control in Owode Yewa, Ogun State, Nigeria - Olusola, Ojo Oladimeji; Adewale, Adejugbagbe John (Asian Review of Environmental and Earth Sciences, 2020)
The increasing challenges of seasonal flood pose serious threat to lives and properties of citizens. This is a major concern for residents in an uncontrolled environment like Owode town in Ogun State. The current study examined a linkage between land use planning and flood control in Owode town. Utilizing a systematic sampling technique, a structured questionnaire was administered to 191 household heads in the study area. The data was analysed with logit Regression model and Marginal Effects at 5% level of significance. The result points out the significance of good road network (Beta= 0.056; p = 0.008) better drainage system (Beta= 0.024; p = 0.000), planned environment (Beta= 0.023; p = 0.000), and public awareness (Beta= 0.016; p = 0.011) as land use planning measures to completely stop flood occurrences in Owode town. Thus, an integration of these measures can sustainably reduce flood risk in flood prone towns like Owode. The study therefore recommends the need for government to re-evaluate its environmental policies to control both human activities and natural habitats.